Agreement on the Continued Application and Amendment of the Convention between the Government of the United Kingdom of Great Britain and Northern Ireland and the Government of the Kingdom of Norway Providing for the Reciprocal Recognition and Enforcement of Judgments in Civil Matters signed at London on 12 June 1961, Oslo, 13 October 2020. ([2020-11-04]) - Unknown
No abstract available